THE EFFECT OF WEBBING STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION AT THE TENTH GRADE OF MAS MUHAMMADIYAH SEI APUNG JAYA - Azlina, Dea (Faculty of Tarbiyah nad Teacher Training, 2021)
This study was conducted to find out effect of using webbing strategy on students’ reading comprehension in. The objective of the study is to find out whether any significant effect of using webbing strategy on students’ reading comprehension at the tenth grade of MAS Muhammadiyah Sei Apung Jaya. The method of this research was quantitatitave research. This quantitative research used quasi-experimental design. The population of the study was the tenth grade of MAS Muhammadiyah Sei Apung Jaya which consisted of 56 students. While, the sample of this research was consisted of experimental group and controlled group, each group consisted of 28 students. The experimental group taught by using webbing strategy, while the controlled group without webbing strategy. The instrument of collecting data was tests (pre-test and post-test) and doccumentation. The data were analysed used preliminary tests and T - test. In conclusion, webbing strategy can give significant effect tn students’ improvement inreading comprehension. The mean score of post-test in experimental group is 88,03, meanwhile the mean score of post-test in controlled group is 62,86. Beside that, the significant effect can be seen in the hypothesis test, which Tobserved is higher than Ttable, ( 9,186 > 1,673 ) in the level of degree α is in significant 0,05. It means that there was significant effect of using webbing strategy to improve students’ reading somprehension at the Tenth grade of MAS Muhammadiyah Sei Apung Jaya